Investigation of the effect of steel fibers on the shear crack-opening and crack-slip behavior of prestressed concrete beams using digital image correlation. (15th August 2019) - Lakavath, Chandrashekhar; Joshi, Suhas S.; Prakash, S. Suriya
Highlights: DIC technique is used to understand crack width and crack slip behavior under shear loads. Effect of steel fibers (0.5%, 1.0%) on the shear behavior of prestressed beams is studied. Full-scale tests at a/d ratio of 2.4 are conducted to understand the effect of fibers on shear. Dilatant behavior is similar for beams with and without fibers up to peak load. Steel fibers reduced the crack opening and crack slip in the post-peak region. Failure mode changed from brittle shear to less brittle flexure-shear with fiber addition. Abstract: The effect of steel fiber reinforcement on the shear behavior of prestressed concrete beam is studied using digital image correlation (DIC) technique. Steel fiber reinforced prestressed concrete (SFRPC) beams with fiber dosages of 0.5% and 1.0% by volume were cast and tested under shear. SFRPC beams were tested under a three-point bending configuration at a shear span ( a ) to depth ( d ) ratio of 2.4 to simulate shear dominant behavior. Other parameters such as compressive strength of concrete, prestressing reinforcement ratio and level of prestressing were kept constant. The kinematics of diagonal shear cracks including crack opening and crack slip were monitored using DIC based full-field strain measurement technique. The improvement in aggregate interlock and residual tensile strength at the crack tip due to the addition of steel fiber was reflected in the post-peak response of SFRPC beams. DIC analysis revealed that the full depth crack was formed in all the SFRPC beams before reaching their peak loads. The dilatant behavior was found to be consistent for all the test specimens (control and fiber reinforced concrete beams) up to peak load. The test results portray that the addition of steel fibers stiffens the post-peak response and reduces the crack opening and crack slip. Moreover, the failure mode changed from shear (brittle) to flexure-shear (less brittle) mode.